The Effect of Problem Solving Learning Models on Students' Understanding of Physics Concepts - Apriani Sijabat; Herna Febrianty Sianipar; Theresia Monika Siahaan; Osco P. Sijabat (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The goal of this study is to see how problem-solving learning paradigms affect students' grasp of physics ideas. This study is a quasi-experimental study. The sample was chosen using the cluster random class methodology, which consisted of two classes, the first of which was taught using a problem-solving learning model and the second of which was taught using traditional methods. Experiment classes provide problem-solving opportunities to help students better understand physics ideas, while control classes are taught in a traditional manner. Pre- and post-test results from students in both classes were used to collect data. The two-way Anava-test was applied, and the level of significance was found to be 0.000 (sig. 0.05), indicating that problem solving learning is beneficial in improving students’ understanding of physics concepts.